Violent relaxation in the Hamiltonian mean field model: II. Non-equilibrium phase diagrams. Issue 1 (31st January 2022) - Santini, Alessandro; Giachetti, Guido; Casetti, Lapo
Abstract: A classical long-range-interacting N -particle system relaxes to thermal equilibrium on time scales growing with N ; in the limit N → ∞ such a relaxation time diverges. However, a completely non-collisional relaxation process, known as violent relaxation, takes place on a much shorter time scale independent of N and brings the system towards a non-thermal quasi-stationary state (QSS). A finite system will eventually reach thermal equilibrium, while an infinite system will remain trapped in the QSS forever. For times smaller than the relaxation time, the distribution function of the system obeys the collisionless Boltzmann equation, also known as the Vlasov equation. The Vlasov dynamics are invariant under time reversal so that they do not 'naturally' describe the relaxational dynamics. However, as time grows the dynamics affect smaller and smaller scales in phase space, so that observables not depending upon small-scale details appear as relaxed after a short time. Herewith we present an approximation scheme able to describe violent relaxation in a one-dimensional toy-model, the Hamiltonian mean field. The approach described here generalizes the one proposed in Giachetti and Casetti (2019 J. Stat. Mech. 043201), which was limited to 'cold' initial conditions, to generic initial conditions, allowing us to predict non-equilibrium phase diagrams that turn out to be in good agreement with those obtained from the numerical integration of the Vlasov equation.